Landscape analysis of m6A modification regulators reveals LRPPRC as a key modulator in tubule cells for DKD: a multi-omics study - Jiang, Li; Yu, Hongda; Jian, Jie; Sai, Xulin; Wang, Yudian; Zhang, Yufei; Wu, Xiai (Frontiers in Pharmacology, 2025)
BackgroundDiabetic Kidney Disease (DKD) is a serious complication of diabetes, imposing a substantial medical burden. The significance of N6-methyladenosine (m6A) modification in the pathogenesis of DKD has become increasingly prominent.AimThis study aimed to investigate the specific expression patterns of the m6A geneset in the pathogenesis of DKD.MethodBulk RNA, single-cell and spatial transcriptome were utilized to clarify the hub gene. 3 types of machine learning algorithms were applied. The possible compounds were screened based on the DSigDB database.ResultGSEA has revealed the potential m6a-associated pathways such as cGMP-PKG pathway. GSVA showed that the two types of m6a regulation, namely m6a-readers and m6a-writers, were generally suppressed in DKD patients. The output of 3 types of machine learning algorithm and differential analysis has determined the LRPPRC as the hub gene. LRPPRC was downregulated in the LOH, PODO, CT, and CD-ICB cell populations, most of which were tubular cells. It exhibited the decreasing trend over time, particularly pronounced in LOH cells. The low activity of LRPPRC was mainly detected in the injured renal tubules. In clinical patients, the expression levels of LRPPRC mRNA in DKD showed the tendency to be downregulated and exhibited the potential correlations with Glomerular Filtration Rate (GFR) and proteinuria according to the Nephroseq database. The lobeline might be an important potential compound involved in the regulation of LRPPRC and other m6a genes. Its actual efficacy needs to be verified in vivo or in vitro.